2009
DOI: 10.1104/pp.109.144626
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate (Pi) Starvation Effect on the Cytosolic Pi Concentration and Pi Exchanges across the Tonoplast in Plant Cells: An in Vivo 31P-Nuclear Magnetic Resonance Study Using Methylphosphonate as a Pi Analog

Abstract: In vivo 31P-NMR analyses showed that the phosphate (Pi) concentration in the cytosol of sycamore (Acer pseudoplatanus) and Arabidopsis (Arabidopsis thaliana) cells was much lower than the cytoplasmic Pi concentrations usually considered (60–80 μm instead of >1 mm) and that it dropped very rapidly following the onset of Pi starvation. The Pi efflux from the vacuole was insufficient to compensate for the absence of external Pi supply, suggesting that the drop of cytosolic Pi might be the first endogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 56 publications
4
139
1
Order By: Relevance
“…Green arrows represent range of productive operating condition for each of the ATPases shown. Red circles represent examples of reported stoichiometry and physiological conditions (42,48,60,61,(63)(64)(65)(66)(67). The diagonal represents equilibrium behavior where the efficiency, as defined in the text, is maximum but the rate of synthesis or pumping would vanish.…”
Section: Kinetic Equivalence Of Pmf Components May Depend On Experimementioning
confidence: 99%
“…Green arrows represent range of productive operating condition for each of the ATPases shown. Red circles represent examples of reported stoichiometry and physiological conditions (42,48,60,61,(63)(64)(65)(66)(67). The diagonal represents equilibrium behavior where the efficiency, as defined in the text, is maximum but the rate of synthesis or pumping would vanish.…”
Section: Kinetic Equivalence Of Pmf Components May Depend On Experimementioning
confidence: 99%
“…The level of E4P was estimated assuming that the TRK reaction with E4P and GAP is at equilibrium, and individual levels of Xu5P and Ru5P were estimated by assuming that RPE is at equilibrium. The D r G for the combined reactions of GAPDH and PGK was estimated using measured values of 3PGA and GAP, assuming an NADPH/NADP ratio of 1 (Heineke et al, 1991) and a P i concentration of 0.002 M (Pratt et al, 2009). Nonaqueous fractionation (Dietz and Heber, 1984) and subcellular fractionation by membrane filtration of chloroplasts have shown that the ATP/ ADP ratios in the plastid are much lower than those in the cytosol (Stitt et al, 1982;Gardeström and Wigge, 1988).…”
Section: Calculation Of Gibbs Free Energy Allows the Identification Omentioning
confidence: 99%
“…The triple KO mutant and wild-type plants were analyzed by the 31 P NMR technique, which can detect several phosphoruscontaining compounds either in living plants or cell extracts (Bligny et al, 1990;Pratt et al, 2009). The drawback of this technique is that it requires large quantities of biological material.…”
Section: Triple Ko Mutant Does Not Mimic or Amplify Phenotypes Causedmentioning
confidence: 99%